Immunological diagnosis of human angiostrongyliasis due to Angiostrongylus cantonensis (Nematoda: Angiostrongylidae) - Eamsobhana, Praphathip; Yong, Hoi Sen (Elsevier, 2009)
Angiostrongylus cantonensis-associated eosinophilic meningitis in humans has been commonly reported worldwide. However parasitologically confirmed cases are not common, as the parasite has been recovered only infrequently from the cerebrospinal fluid of patients. The potential value of immunodiagnosis is therefore self-evident. Immunological tests can also help in the differential diagnosis of parasitic (particularly helminths) infections that cause eosinophilic meningitis. This paper summarizes the state of and advances in the immunological diagnosis of human angiostrongyliasis due to Angiostrongylus (= Parastrongylus) cantonensis. A specific antigen is available for the definitive diagnosis and unequivocal differentiation of eosinophilic meningitis due to helminth infections. Rapid diagnostic kits based on dot-blot ELISA have been developed and have proved to be simple, effective, and economical for field use.